2007
DOI: 10.1111/j.1462-5822.2006.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherent-invasive Escherichia coli isolated from Crohn's disease patients induce granulomas in vitro

Abstract: SummaryAdherent-invasive Escherichia coli (AIEC) have been shown to be highly associated with ileal Crohn's disease (CD). AIEC survive within infected macrophages, residing within the phagolysosomal compartment where they take advantage of the low pH to replicate extensively. We investigated whether, like the tuberculous bacillus which also persists within macrophages, AIEC LF82 induces the formation of granulomas, which are a common histopathological feature of CD. For this purpose, we have taken advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…A possible role for AIEC in the etiopathogenesis of CD in susceptible hosts is summarized in Figure 1. The sequential steps involved in the induction of disease by the bacteria are: (1) abnormal colonization via binding to the CEACAM6 receptor, which is overexpressed in the ileal mucosa of CD patients [13] ; (2) ability to adhere to and to invade intestinal epithelial cells, which allows bacteria to cross the mucosal barrier [37] ; (3) survival and replication within infected macrophages in the lamina propria; and (4) induction of TNF-α secretion [45] and granuloma formation [58] . AIEC strains could colonize the ileal mucosa of CD patients by binding to CEACAM6, translocate across the human intestinal barrier to move into deep tissues, and once there, continuously activate immune cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible role for AIEC in the etiopathogenesis of CD in susceptible hosts is summarized in Figure 1. The sequential steps involved in the induction of disease by the bacteria are: (1) abnormal colonization via binding to the CEACAM6 receptor, which is overexpressed in the ileal mucosa of CD patients [13] ; (2) ability to adhere to and to invade intestinal epithelial cells, which allows bacteria to cross the mucosal barrier [37] ; (3) survival and replication within infected macrophages in the lamina propria; and (4) induction of TNF-α secretion [45] and granuloma formation [58] . AIEC strains could colonize the ileal mucosa of CD patients by binding to CEACAM6, translocate across the human intestinal barrier to move into deep tissues, and once there, continuously activate immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…Using an in vitro model of human granuloma [57] , CD-associated AIEC LF82 were reported to induce aggregation of infected macrophages, some of which fused to form multinucleated giant cells and subsequent recruitment of lymphocytes. Analysis of the cell aggregates indicated that they are very similar to the early stages of epithelioid granulomas [58] .…”
Section: Granuloma Formationmentioning
confidence: 95%
“…23 This probably results in the formation of granulomas, as observed with the in vitro model of human granulomas, in which AIEC LF82 induces aggregation of infected macrophages, and sometimes their fusion to form multinucleated giant cells, and subsequent recruitment of lymphocytes. 26 Secretion of TNF-a by infected monocytes/macrophages is a common feature of pathogenic bacteria, but impaired macrophage TNF-a secretion has been reported following infection with some of them such as Brucella spp., meningitidis-associated E. coli K1, and Francisella tularensis. [27][28][29] In addition, TNF-a can have opposite effects on intracellular bacteria replication.…”
mentioning
confidence: 99%
“…By expressing long polar fimbriae, the bacteria interact with mouse and human Peyer's patches and translocate across microfold cells monolayers (83). AIEC are also able to survive and replicate extensively within a large, phagolysosome-like vacuole in macrophages (84) and AIEC-infected macrophages aggregate and fuse to form multinucleated giant cells in vitro (85).…”
Section: Gut Microbiotamentioning
confidence: 99%